THE STRATEGY OF ISLAMIC DAKWAH IN THE ERA OF GLOBALIZATION AND MODERNIZATION USING SOCIAL MEDIA - Rubino; Dian Indah Multazam (Sean Institute, 2022)
In this era of globalization and digitalization, preaching activities are very important to be used as a guide to avoid the bad effects of digitalization and globalization. Today's preaching activities need to use social media management fiqh. This research is literature research which is one of the qualitative studies which in general does not require researchers to go directly to the field when looking for sources of information. Source The research used in this paper is written works, including the results of studies that have or have not been published. Examples of literature review include research on the ideas of figures, history, review (research) of books and various other types of research related to literature study. Social media has become a means of preaching that is needed by preachers, this is due to the rapid development of information and communication technology.